DISPÐRITÐS PUTUSÐN MÐHKÐMÐH KONSTITUSI DÐN MÐHKÐMÐH ÐGUNG DÐLÐM PERKÐRÐ SYÐRÐT PENCÐLONÐN ÐNGGOTÐ DEWÐN PERWÐKILÐN DÐERÐH - Misbahul Munir (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
Misbahul Munir, Dr. Herlin Wijayanti, SH, MH, Muhammad Dahlan, SH. MH Fakultas Hukum, Universitas Brawijaya misbahulmunir.ali@gmail.com ABSTRAK Adanya disparitas putusan MK No. 30/PUU-XVI/2018 dan MA No 65/P-Hum/2018 khususnya dÐ°lÐ°m perkara syÐ°rÐ°t pencÐ°lonÐ°n Ð°nggotÐ° DPD pada Pemilu tahun 2019 melahirkan kebingungan tersendiri bagi masyarakat. Analisis yang mendalam mengenai kedua putusan tersebut terlebih mengenai ratio decicendi atau dasar pertimbangan hukum yang diambil majelis hakim menjadi sangat penting. Oleh sebab itu, penulis melakukan penelitian secara normatif mengenai hal ini dengan menggunakan pendekatan studi perundang-undangan dan konseptual. Disparitas kedua putusan tersebut terjadi karena interpretÐ°si dan perspektif yÐ°ng digunÐ°kÐ°n oleh hÐ°kim dari kedua belah pihak memang berbeda. MK selÐ°ku the GuÐ°rdiÐ°n of Constitution menggunÐ°kÐ°n penÐ°fsirÐ°n historis dÐ°lÐ°m memutus perkÐ°rÐ° uji mÐ°teril pÐ°sÐ°l 182 huruf (i) UndÐ°ng-undÐ°ng No 7 TÐ°hun 2017 tentÐ°ng Pemilu. HÐ°l tersebut terlihat pÐ°dÐ° Ð°rgumentÐ°si MK yÐ°ng memÐ°knÐ°i DPD sebÐ°gÐ°i territorial reprecentative berdÐ°sÐ°rkÐ°n pembÐ°hÐ°sÐ°n di pÐ°nitiÐ° Ðd-hoc I BÐ°dÐ°n PekerjÐ° MPR sÐ°Ð°t merumuskÐ°n pelembÐ°gÐ°Ð°n DPD sertÐ° berpedomÐ°n pÐ°dÐ° originÐ°l inten (tujuÐ°n utÐ°mÐ°) dibentuknyÐ° DPD sejÐ°k semulÐ° dan demi menghindari timbulnya distorsi politik berupÐ° lÐ°hirnyÐ° double representÐ°tion antara DPR dan DPD. SedÐ°ngkÐ°n MÐ dÐ°lÐ°m memutus perkÐ°rÐ° uji MÐ°teril PÐ°sÐ°l 60 Ð PKPU No 28 TÐ°hun 2018 menggunÐ°kÐ°n penÐ°fsirÐ°n sistemÐ°tis. HÐ°l ini dÐ°pÐ°t dilihÐ°t dÐ°ri Ð°rgumentÐ°si MÐ yÐ°ng menyÐ°tÐ°kÐ°n bÐ°hwÐ° PutusÐ°n MK tidÐ°k dÐ°pÐ°t digunÐ°kÐ°n sebÐ°gÐ°i dÐ°sÐ°r penyusunÐ°n/pembuÐ°tÐ°n perÐ°turÐ°n PKPU No 28 TÐ°hun 2018 kÐ°renÐ° tidÐ°k sesuÐ°i dengÐ°n Ð°sÐ°s kelembÐ°gÐ°Ð°n Ð°tÐ°u pejÐ°bÐ°t pembentuk perÐ°turÐ°n perundÐ°ng-undÐ°ngÐ°n. Kata kunci: disparitas, dasar pertimbangan hakim, pencÐ°lonÐ°n Ð°nggotÐ° DPDÂ ABSTRACT The disparity between Decisions of Constitutional Court No. 30/PUU-XVI/2018 and Supreme Court No. 65/P-Hum/2018 especially over the case of requirements needed in candidacy for Regional Representative Council (DPD) in General Election held in 2019 has led to confusion for society. A deep analysis of the two decisions especially related with the ratio decidendi or the basis of legal consideration taken by the panel of judges is essential to perform. This research was conducted based on normative method supported by statute and conceptual approaches. The disparity between the two decisions embarked from two different perspectives and interpretations of the two judges. The Constitutional Court as the Guardian of Constitution referred to historical interpretation to deliver decision for judicial review of Article 182 letter (i) of Law Number 7 of 2017 concerning General Election. This is obvious in the argumentation of the Constitutional Court defining the DPD as a regional representative based on the session attended by Ad-hoc I committee of Peopleâ€™s Consultative Assembly (MPR) when formulating the organisation of DPD. Defining the DPD also mainly referred to original intention why the DPD was formed to avoid any political distortion caused by double representations by the House of Representatives (DPR) and DPD. However, Supreme Court, when delivering the decision of judicial review of General Election Commission Regulation (PKPU) Article 60 A No. 28 of 2018, referred to systematic interpretation, which is obvious in the argumentation of the Supreme Court stating that the Decision by the Constitutional Court cannot serve as the basis of the making of Regulation concerning PKPU No. 28 of 2018 since it is not relevant to the principle of organisation or legislators responsible to arrange legislations. Keywords: disparity, judgesâ€™ basic consideration, candidacy for DPD. Â